Soil stabilization studying of tropical brazilian soil by unconfined strength compression tests - Ide, Daniela Massami [UNESP]; Peixoto, Anna Silvia Pacheco [UNESP]; Macedo, Sérgio Silva [UNESP] (My University, 2007)
The tropical soils exhibit a unique mechanical behavior due to their genesis, with a partially saturated condition, and are very dependent on the degree of weathering. The term tropical soil includes both lateritic and saprolitic soils. Another peculiarity of those soils is the collapsibility: loose the bulk when they get wet and increase their load. In Brazil, this is a common problem of pavements. A solution is the stabilization of the soil with calcitic lime. This paper explains a study based on unconfined strength compression tests of a lateritic and collapsible sandy soil mixed with calcitic lime CH-III and the ash-lime. The cure periods studied were: 7, 14 and 28 days. The results show an increasing gain in resistance of the mixtures in comparison with the natural soil. In addition, it was observed that, in the optimum moisture content, there was not any significant difference in the cure periods of 14 and 28 days. Throughout the preliminary results, it can be seen that the content of 6% would be the best indication to stabilize the soil studied.
Keywords: Mixture; Soil-ash-lime; Soil-lime; Unconfined compression test